Pharmacogenetics as part of recommended precision medicine for tuberculosis treatment in African populations: Could it be a reality? - Carola Oelofse; Carene Anne Alene Ndong Sima; Marlo Möller; Caitlin Uren (Wiley, 2023)
Abstract Globally, tuberculosis (TB) is the second most lethal infectious disease. However, in sub‐Saharan Africa, TB has the largest disease burden, with drug‐resistant TB increasingly becoming a concern. The social and economic impact of TB should not be overlooked, especially in areas where healthcare systems are overburdened, and resources need to be allocated judiciously. The aim of pharmacogenetics (PGx) is to improve therapeutic response and to minimize adverse drug reactions by selecting the most optimal drug and dosage for the individual patient. Implementation of PGx into routine clinical care has been slow, especially in resource‐limited settings, because of perceived high costs relative to uncertain benefit. Given the impact of TB on the disease and disability burden in these regions, a better understanding and optimization of TB treatment in understudied African populations is vital. The first weeks of treatment are the most crucial for treatment success, and a point‐of‐care pre‐emptive PGx test could start patients on the most bactericidal and least toxic drug combination. This may potentially reduce the number of patients returning to clinical care and streamline the use of limited resources across the healthcare system. This review explores the status of TB PGx in Africa, the utility of existing TB PGx testing panels, and the economic feasibility in developing a clinically valuable, cost‐effective, pre‐emptive PGx test to guide optimized, new dosing regimens specifically for African population groups. TB is a disease of poverty, but investment in PGx research in African populations could ensure improved treatments and long‐term cost savings.